Forced sustained swimming exercise at optimal speed enhances growth of juvenile yellowtail kingfish (Seriola lalandi) - Palstra, Arjan P.; Mes, Daan; Kusters, Kasper; Roques, Jonathan A. C.; Flik, Gert; Kloet, Kees; Blonk, Robbert J. W. (Frontiers in Physiology, 2015)
Swimming exercise at optimal speed may optimize growth performance of yellowtail kingfish in a recirculating aquaculture system. Therefore, optimal swimming speeds (Uopt in m s-1 or body lengths s-1, BL s-1) were assessed and then applied to determine the effects of long-term forced and sustained swimming at Uopt on growth performance of juvenile yellowtail kingfish. Uopt was quantified in Blazka-type swim-tunnels for 145 mm, 206 mm and 311 mm juveniles resulting in values of: 1) 0.70 m s-1 or 4.83 BL s-1, 2) 0.82 m s-1 or 3.25 BL s-1 and 3) 0.85 m s-1 or 2.73 BL s-1. Combined with literature data from larger fish, a relation of Uopt (BL s-1) = 234.07(BL)-0.779 (R2= 0.9909) was established for this species. Yellowtail kingfish, either forced to perform sustained swimming exercise at an optimal speed of 2.46 BL s-1 (‘swimmers’) or allowed to perform spontaneous activity at low water flow (‘resters’) in a newly designed 3,600 L oval flume (with flow created by an impeller driven by an electric motor), were then compared. At the start of the experiment, ten fish were sampled representing the initial condition. After 18 days, swimmers (n= 23) showed a 92% greater increase in BL and 46% greater increase in BW as compared to resters (n= 23). As both groups were fed equal rations, feed conversion ratio (FCR) for swimmers was 1.21 vs. 1.74 for resters. Doppler ultrasound imaging showed a statistically significant higher blood flow (31%) in the ventral aorta of swimmers vs. resters (44 ± 3 mL min-1 vs. 34 ± 3 mL min-1, respectively, under anesthesia). Thus growth performance can be rapidly improved by optimal swimming, without larger feed investments.